Unexpected amaurosis occurring after peribulbar anesthesia: Exploring the causes in two cases. Issue 1 (January 2022) - Rezkallah, Amina; Gargori, Nezar; Denis, Philippe; Waldmann, Véronique; Mathis, Thibaud; Kodjikian, Laurent
Peribulbar anesthesia (PB) is known to be safer than retrobulbar (RB) anesthesia. To our knowledge, no amaurosis has been described after PB. We report here the cases of two patients who underwent PB before membrane peeling. The injections were administered with a 25-gauge, 22-mm bevel disposable needle. The anesthetic used was ropivacaine 1% with a volume of 8 ml and 75 µg of clonidine as an adjuvant (7.5 µg/ml). Given that complete akinesia was not achieved, a second injection of 2 ml was administered in the supero-medial injection site. Thirty minutes after the PB, the first patient experienced amaurosis with no light perception (LP). The ophthalmic examination was normal. Visual acuity recovered after 1 day. Regarding the second patient, the loss of VA was observed 20 min after the PB. IOP was 20 mmHg. The anterior segment and fundus exam were normal. Rubin found the PB technique to be as effective and safer than RB injection, as the needles are not supposed to enter the RB space and Davis and Mandel found no amaurosis after PB. PB is administered via the extraconal injection of an anesthetic agent. These amaurosis might be explained by the fact that some anesthetic may have penetrated the RB space. In cases where two PB injections are administered, the anatomy is expected to change due to the volume effect of the first injection. The second injection is higher risk as it is administered closer to the optic nerve.